A influência dos componentes do processamento fonológico na escrita de numerais arábicos e tipos de erros - Luana Teixeira Batista (2023)
Number transcoding refers to the ability to establish relationships and make conversions between verbal and Arabic numeric representations. It is an essential numerical skill and indicates later mathematical performance. The main objective of this dissertation was to investigate the role of phonological processing in the Arabic number writing and their types of errors. First, the introduction describes the current state of the literature, in relation to the most relevant cognitive models of number transcoding, their impact on mathematics and the association between language and Number transcoding. In chapter 2, a systematic review of the literature analyzed the types of errors in Arabic number writing made by children, most described in the literature, the impact of idiomatic specificities of numerical words and the relationship of the types of errors with cognitive mechanisms, especially the phonological processing. The results showed that, in addition to lexical, syntactic, and combined, there are subclassifications within the types of lexical and syntactic errors. An important type of error consistently found in the literature is the inversion error, which occurs in languages where the verbal number system is inverted in relation to the Arabic one. Regarding cognitive mechanisms, studies point to an association between transcoding and types of errors with working memory. However, the results are still inconclusive and there are no studies that assess the components of phonological processing in the Arabic number writing and types of errors. Considering the results of the review, in chapter 3 we investigate the specific contribution of the three components of phonological processing (ie, phonological working memory, phonemic awareness, and lexical access speed), in addition to visuospatial working memory, on the overall performance of transcoding and types of errors. The results showed that the overall transcoding performance was selectively associated by the components of phonological processing, by phonemic awareness and lexical access speed. Furthermore, lexical errors were associated with phonemic awareness and lexical access, while syntactic and combined errors were associated with phonemic awareness and visuospatial working memory. In chapter 4 we present the conclusion of the dissertation and the theoretical and practical implications of the studies.